Development of Civics Learning through COLAKTRA (Congklak Nusantara) Innovation as a Traditional Game-Based Learning Media - Ardi Afriansyah; Dikdik Baehaqi Arif; Kireida Rona Islam (Yayasan Insan Mulia Bima, 2024)
This research aims to investigate the use of the traditional game Congklak as a creative and educational learning medium in the context of Citizenship Education (PKn). The research method uses a literature review approach, by summarizing literature that is relevant to the research topic with the analytical model used in this literature review method involving several stages, namely sample selection, validation and review, data collection, data processing and analysis and preparation of a conceptual framework, which can served. The focus is on analyzing the benefits and implications of using Congklak Nusantara (COLAKTRA) in Civics learning. The results show that Congklak has an important role in children's development, supporting their physical, mental, intellectual and spiritual growth. The use of Congklak in Civics learning through COLAKTRA increases student involvement and creates a pleasant learning atmosphere. The integration of Civics values ​​into Congklak makes it a medium that invites players to reflect on and appreciate Indonesia's cultural riches. The conclusion of this research confirms that COLAKTRA is not just a game, but also an effort to preserve cultural heritage and form a generation that loves the country. It is hoped that the use of traditional games in Civics learning can help students understand and experience the diversity of Indonesia, so that they become competent citizens. Thus, COLAKTRA has the potential to be an effective tool in achieving the goals of citizenship education.